Exploring students' mathematical performance, metacognitive experiences and skills in relation to fundamental theorem of calculus. Issue 7 (1st November 2017) - Radmehr, Farzad; Drake, Michael
ABSTRACT: Several studies have explored students' understanding of the relationships between definite integrals and areas under curve(s). So far, however, there has been less attention to students' understanding of the Fundamental Theorem of Calculus (FTC). In addition, students' metacognitive experiences and skills whilst solving FTC questions have not previously been explored. This paper explored students' mathematical performance, metacognitive experiences and metacognitive skills in relation to FTC questions by interviewing nine university and eight Year 13 students. The findings show that several students had difficulty solving questions related to the FTC and that students' metacognitive experiences and skills could be further developed.